STUDY ON CRACK GROWTH OF AN ENGINE TURBINE - LIU ZongHui; CHENG XiaoMing; SHAN XiaoMing; GUO XiaoJun (Jixie qiangdu)
According to the damage tolerance design requirements to the engine life-limited parts,research on the fatigue crack growth tests of an engine power turbine（ high-strength GH4169） is carried out in this article. The crack growth behaviors of the turbine and the dispersion are obtained. Meanwhile,the three-dimension crack growth simulation is conducted and the results are compared with the test results. The result demonstrates that the crack propagation simulation result of the turbine has high accuracy,the analysis method has the value of engineering application.